Preparing Teacher Educators in Reading - Allington, Richard ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
One of the most frequent criticisms of doctoral preparation in reading is the lack of training and guidance in the area of teacher education. Often graduate students are assigned as teaching assistants, either initially assuming full responsibility for selected undergraduate sections with little preparation or else beginning by assisting a professor in a course, assuming primary responsibility for a section of the course later on. A couple of strategies which might be initiated to strengthen the teacher education component of doctoral preparation are the seminar, like the one developed and offered at the State University of New York at Albany in the summer of 1974, and a practicum which has yet to be initiated although selected components are operational. (Outlines of the seminar--with lists of references, sample modules, and audiotapes--and the practicum are included.) (JM)
ERIC Note: Unpublished study prepared at SUNY at Albany, Department of Reading; Not available in hard copy due to marginal legibility of original document.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Doctoral Programs; Higher Education; Institutes (Training Programs); Reading; Reading Instruction; Seminars; Summer Programs; Teacher Education; Teacher Education Curriculum; Teacher Educator Education; Reports, Research